Modulation of VO2 Metal–Insulator Transition by Ferroelectric HfO2 Gate Insulator. (20th March 2020) - Yajima, Takeaki; Nishimura, Tomonori; Tanaka, Takahisa; Uchida, Ken; Toriumi, Akira
Abstract: Ferroelectric gating of functional materials has often suffered because ferroelectric materials are poor insulators. In this study, the recently reported ferroelectric HfO2, a large band‐gap oxide with excellent insulating properties, is exploited for electrostatically gating the archetypical metal–insulator transition material, VO2 . By protecting the meta‐stable ferroelectric phase from deterioration, the ferroelectric gating is successfully demonstrated with an ultra‐thin VO2 channel in the back‐gate geometry. The observed modulation of the VO2 channel conductivity is originated from the ferroelectric polarization reversal in the HfO2 gate insulator combined with the VO2 metal–insulator transition. These results demonstrate the significant potential of ferroelectric HfO2 for electrostatically controlling the state of matter for both fundamental research and device application. Abstract : Ferroelectric gating of functional materials has often suffered because ferroelectric materials are poor insulators. Here, the recently reported ferroelectric HfO2, a large band gap oxide with an excellent insulating property, is exploited for electrostatically gating the archetypical metal–insulator transition material, VO2 . The results demonstrate the significant potential of ferroelectric HfO2 for electrostatically controlling the state of matter.